Subcutaneous Emphysema: A Rare Postoperative Complication after Tonsillectomy (Journal of Paediatric Surgeons of Bangladesh, 2015)
Tonsillectomy is considered as a relatively safe procedure. This report aimed at describing an uncommon complication of this surgical procedure - subcutaneous emphysema. A 12 years old girl admitted for tonsillectomy operation. After routine preoperative assessment her operation was performed under general anesthesia. Surgery was uneventful. 7-8 hours after surgery, during follow-up in postoperative room progressing subcutaneous emphysema was noticed which initially involved the neck. But later on, it extended upper chest, upper arms, face & back. Crepitus swelling of neck and bilateral parotid region, typical of subcutaneous emphysema was noted. Chest X ray showed free air in the cervical regions reaching upper mediastinum. There was no airway obstruction and patients general condition was stable. Emphysema was no longer clinically evident 3 days after & patient was released. Subcutaneous emphysema is an uncommon complication of tonsillectomy, appearing almost ever after deeper dissections of the pharyngeal mucosa, when a porous surface is created, thus providing a route for the entry of air. Increased upper airway pressure may contribute to this injury.J. Paediatr. Surg. Bangladesh 3(1): 51-53, 2012 (January)